The effect of interest rates on loan repayment - Nassozi Susan Rhita (My University, 2023)
The research was carried out to study the effect of interest rates on loan repayment in Uganda's commercial banks with specific regard to Centenary Bank, to establish the factors responsible for the increase of interest rates, to establish the factors leading to defaulting of loan payments, and to analyze the relationship between interest rates and loan repayment in Uganda’s commercial Banks a case study of Centenary Bank, Mukono Branch. The study established that most Centenary Bank customers were aware of the influence interest rates have on micro-credits in regard to business performance. It was established that the provision of loans to entrepreneurs has a great impact on the business’s performance. This partly explains unenthusiastic regard of the management of Uganda Micro Finance Institutions to their improvements, in the credit terms to their client’s entrepreneurs. The study also established the most important cause of poor business performance and collapse as being amongst others the high interest rates, limited amount lent, lack of entrepreneurship skills and high taxes. The researcher recommends that Centenary Bank should endeavor to conduct some entrepreneurship skills and loan servicing short training workshops if it’s to meet its objectives. It should also revise its terms of lending and reduce on the interest rates to enable entrepreneurs make profits and be able to service their loans as this will lead to the growth and continuity of their businesses.